On the Role of Chinese English as a Foreign Language: Teachers’ Well-Being and Loving Pedagogy in Their Academic Engagement - Li, Bo; Miao, Guoxin (Frontiers in Psychology, 2022)
Positive emotions are regarded as vital issues in EFL instruction. This study attempted to consider the relationships between Chinese EFL teachers’ psychological well-being, loving Pedagogy, and work engagement as the constructs of positive psychology in academic contexts. It also tried to examine the contribution of psychological well-being and loving pedagogy in work engagement. To this end, 414 Chinese EFL teachers including participated in this study. The three questionnaires called Dispositions towards Loving Pedagogy (DTLP) Scale, Index of Psychological Well-Being at Work (IPWBW), and Self-report Engagement Questionnaire were distributed among learners. The findings showed significant relationships between well-being, loving pedagogy, and work engagement. Moreover, the results indicated that teachers’ psychological well-being significantly predicted their work engagement. This study provided some implications for teachers, teacher educators, and educational policy-makers to raise their awareness of adopting loving pedagogy and boosting teacher well-being for the enhancement of teacher involvement in academic contexts.